Temperature field in MIG welding of thin plate of stainless steel - Luu, Van Hung; Nguyen, Tien Duong (JST: Engineering And Technology For Sustainable Development, 2021)
The butt weld joint of SUS316L stainless steel is considered in this study. The weld joint is not beveled, has a gap and is welded in one pass by MIG welding process. First, the welding parameters are determined through calculation and test welding for the butt joint of two plates of 3 mm in thickness. Then these welding parameters are used as input date to calculate and determine the temperature field by two methods: The calculation method is based on the theory of heat transfer process and the numerical simulation method of welding processes that relies on SYSWELD software on the basis of the finite element method. Calculation results of two methods were compared with each other and tested by experiment to show the reliability of calculation and simulation results.